Combinação do Mat Pilates e Tai Chi Chuan na melhoria da qualidade do sono em idosos - Corazza, Sara Teresinha (2021)
Sleep disorders, as well as insomnia and excessive daytime sleepiness, are elements that affect the quality of life of the elderly, but there is already strong evidence that these problems can be eliminated or reduced with physical exercise practice. Objective: the improvement in sleep quality was confirmed in a group of elderly people after the combined intervention of Mat Pilates (MPS) and Tai Chi Chuan (TCC). Method: this was a cross-sectional, interventional study with 66 elderly people, with an average age of 66.53 years, who underwent twenty-six sessions of combined practice of MPS and CBT and were submitted to the application of the Quality Index Questionnaire of Pittsburgh Sleep (PSQI) before and after the intervention. The statistical analysis used was the t test for paired samples, using SPSS, in its version 21.0, with a significance level of 5 percent. Results and conclusion: as a result, improvement was obtained in all seven categories of the PSQI, highlighting the efficiency of the combination of MP and TCC for restful and relaxing sleep, thereby improving the quality of life and health of elderly people.